Seasonal dynamics of intestinal microbiota in juvenile Chinese mitten crab (Eriocheir sinensis) in the Yangtze Estuary - Qin, Ze; Wang, Sikai; Wu, Yeling; Sun, Jinhui; Zhao, Feng (Frontiers in Cellular and Infection Microbiology, 2024)
In this study, the seasonal differences in the intestinal microbiota of Chinese mitten crab (Eriocheir sinensis) larvae were investigated at different sites in the intertidal zone of the Yangtze River Estuary. 16S rRNA high-throughput sequencing technology was used to compare and analyze the microbial community structure in the intestines of juvenile crab from different seasons. The results showed that the main microbial phyla in all seasons and sites were Proteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria, which accounted for 97.1% of the total microbiota. Composition analysis revealed that the relative abundance of Proteobacteria decreased from summer to winter at each station, whereas Bacteroidetes showed the opposite trend.Alpha diversity analysis showed that species richness increased from summer to winter at the upstream site (P < 0.05), but decreased at the downstream site (P < 0.05), with no significant differences observed in other comparisons. Biomarker species analysis showed that juvenile crab exhibited a more specialized microbial community in summer compared with autumn and winter. Co-occurrence network analysis revealed that microbial interaction network complexity was lower in autumn compared with summer and autumn. Functional prediction analysis showed that the microbial community only exhibited seasonal differences in amino acid biosynthesis, cofactor, prosthetic group, electron carrier, and vitamin biosynthesis, aromatic compound degradation, nucleotide and nucleoside degradation, and tricarboxylic acid cycle pathways. The results indicated that the microbiota did not significantly differ among sites, and seasonal variation was a main factor influencing the differences in intestinal microbiota of Chinese mitten juvenile crab. Moreover, the microbial community was more complex in summer compared with autumn and winter.